Analisis Teknik Bermain dan Melodi Lagu “Tristezas de um Violão” (Choro Triste No. 1) karya Garoto - Kallu, Juan Kevin; Kadir, Tulus Handra (Universitas Negeri Padang, 2024)
This study analyzes the guitar techniques and melody in Garoto's *